2020
DOI: 10.1021/acsabm.9b01078
|View full text |Cite|
|
Sign up to set email alerts
|

Polypeptide-Templated Au Nanoclusters with Red and Blue Fluorescence Emissions for Multimodal Imaging of Cell Nuclei

Abstract: Noble metal nanoclusters (<2 nm) prepared using special molecules such as proteins and peptides as templates have been attracting increasing attention in biomedical applications and cell imaging because of their excellent biocompatibility, size-dependent fluorescence properties, and relatively simple synthesis. Although cell imaging using metal clusters has developed rapidly in recent years, multimodal imaging of the cell nucleus remains challenging. Herein, we report the successful synthesis of two different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…The fluorescent properties of Au clusters could make them used as fluorescent inks ( Figure 1 C). As depicted in Figure 1 D, the absorption peak position of peptide is located at 275 nm, while the position of the absorption peak of Au clusters is located at 243 and 292 nm, which was the characteristic absorption peaks of peptide-Au clusters [ 42 , 43 ]. As shown in Figure S1 , the peaks of C, Au, S, O, and N were obviously detected by X-ray photoelectron spectroscopy (XPS) spectrum.…”
Section: Resultsmentioning
confidence: 99%
“…The fluorescent properties of Au clusters could make them used as fluorescent inks ( Figure 1 C). As depicted in Figure 1 D, the absorption peak position of peptide is located at 275 nm, while the position of the absorption peak of Au clusters is located at 243 and 292 nm, which was the characteristic absorption peaks of peptide-Au clusters [ 42 , 43 ]. As shown in Figure S1 , the peaks of C, Au, S, O, and N were obviously detected by X-ray photoelectron spectroscopy (XPS) spectrum.…”
Section: Resultsmentioning
confidence: 99%
“…Optimizing synthetic conditions (e.g., light, pH, Au/peptide ratio, reaction time and temperature), Liu et al were able to fine-tune the emission properties of SV-capped gold nanoclusters, obtaining two distinct Au NC families, characterized by blue (λ ex = 320 nm, λ em = 405 nm) and red fluorescence emission (λ ex = 560 nm, λ em = 657 nm), respectively. Such SV-Au NCs exhibited an excellent multimodal imaging ability, enabling dual-color imaging even by naked eye, and moreover, they showed effective peroxidase-like activity in the oxidation of tetramethylbenzidine [64]. The association between CCY domains with self-assembling peptide motifs afforded supramolecular structures of Au NCs with improved luminescence.…”
Section: Peptidesmentioning
confidence: 99%
“…In addition, the targeted imaging of subcellular organelles including mitochondria, nuclei, and nucleoli staining using AuNCs is crucial to modulating the cellular fate and organelle-related diseases. , Fang et al developed mitochondria-targeting peptide (CCYKFR)-templated AuNCs for anticancer treatment with an improved radiosensitization effect . Red and blue fluorescent AuNCs were synthesized using the same polypeptide SV (sequence NH 2 -CCY­GGP­KKK­RKVG-COOH) as a template which possessed the multimodal imaging capability of cell nuclei . Wang et al reported novel AuNCs where the stabilizing ligands were positively charged tripeptides (Lys-Cys-Lys).…”
Section: Mncs and Cqds For Biomedical Applicationsmentioning
confidence: 99%
“…80 Red and blue fluorescent AuNCs were synthesized using the same polypeptide SV (sequence NH 2 -CCYGGPKKKRKVG-COOH) as a template which possessed the multimodal imaging capability of cell nuclei. 82 Wang et al reported novel AuNCs where the stabilizing ligands were positively charged tripeptides (Lys-Cys-Lys). These AuNCs selectively stained nucleoli and enabled the monitoring of nucleolar dynamics during the process of reverse transformation in malignant cells (Figure 7B).…”
Section: ■ Introductionmentioning
confidence: 99%